2022
DOI: 10.1021/acs.energyfuels.2c01722
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength Formed Coke from Torrefied Biomass and Its Blend with Noncaking Coal

Abstract: In continuation of our previous study on production of high-strength metallurgical coke from torrefied softwood (cedar), we studied coke production from a mixture of torrefied cedar (TC) and noncaking coal by pulverization to sizes <100 μm, mixing, binderless hot briquetting, and carbonization. These sequential processes produced coke with a tensile strength of 5–17 MPa, which was equivalent to or greater than that of conventional coke (5–6 MPa), from TC-coal mixtures over the entire ranges of TC mass fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In continuation of the above-mentioned studies by Wibawa et al, 6,12) the present authors have been investigating formed coke production from woody biomass by torrefaction, pulverization, washing with torrefaction-derived acidic water, hot briquetting, and carbonization, as shown in Fig. 1, focusing on the removal of AAEM species by the acid-water washing and examining its effects on the strength and reactivity of the resulting coke.…”
Section: Control Of Reactivity Of Formed Coke From Torrefied Biomass ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In continuation of the above-mentioned studies by Wibawa et al, 6,12) the present authors have been investigating formed coke production from woody biomass by torrefaction, pulverization, washing with torrefaction-derived acidic water, hot briquetting, and carbonization, as shown in Fig. 1, focusing on the removal of AAEM species by the acid-water washing and examining its effects on the strength and reactivity of the resulting coke.…”
Section: Control Of Reactivity Of Formed Coke From Torrefied Biomass ...mentioning
confidence: 99%
“…Wei et al 11) torrefied woody biomass in the presence of acid-catalysts, which greatly enhanced the formation of anhydrosugars. They also converted the torrefied biomass to high-strength coke by applying the sequence proposed by Wibawa et al 6) Wibawa et al 12) also prepared coke from mixtures of non-caking coal and torrefied cedar and demonstrated co-pulverization of the coal and torrefied cedar before briquetting led to coke with a TS as high as 28-32 MPa regardless of the mixing ratio.…”
Section: Control Of Reactivity Of Formed Coke From Torrefied Biomass ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed solutions to this issue are formed coke [7][8][9] and briquette blending carbonization process 10) , which are believed to facilitate particle adhesion by pre-compressing and molding the coal, thereby improving inter-particle bonding. Researchers have explored the use of briquette blended with biomass [11][12][13] , iron ore 14) and non-and slightly coking coals 15) , low volatile non-coking coal 13) , coke breeze 16) and alumina beads 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Torrefaction, hydrothermal treatment, hot briquetting, and combinations of these methods have been proposed as methods for physical treatment of biomass, and it has been shown that the coke produced by these methods has high strength and high gasification reactivity. [9][10][11][12] Although the above methods can also be applied to 100% biomass usage and low-quality coal to give extremely high-strength coke, the coke obtained by these methods is too highly reactive. [13][14][15][16] In terms of chemical treatment methods, there have been studies into binding biomass and low-quality coal by solvent modification, [17][18][19][20][21] and it is possible to manufacture highstrength coke by blending of modified-materials.…”
Section: Introductionmentioning
confidence: 99%